A4NH 2020 annual report highlights: Flagship 4 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
This includes three highlights document for Flagship 4 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: ‘Double-duty’ actions to address malnutrition in all its forms Highlight 2: Convening regional stakeholders around nutrition Highlight 3: Determining the cost-effectiveness of multisectoral interventions